Antimicrobial peptides and proteins as alternative antibiotics for porcine semen preservation - Ros-Santaella, Jose Luis; Nový, Pavel; Scaringi, Maria; Pintus, Eliana (BMC veterinary research, 2024)
BACKGROUND: Antimicrobial resistance (AMR) is nowadays a major emerging challenge for public health worldwide. The over- and misuse of antibiotics, including those for cell culture, are promoting AMR while also encouraging the research and employment of alternative drugs. The addition of antibiotics to the cell media is strongly recommended in sperm preservation, being gentamicin the most used for boar semen. Because of its continued use, several bacterial strains present in boar semen have developed resistance to this antibiotic. Antimicrobial peptides and proteins (AMPPs) are promising candidates as alternative antibiotics because their mechanism of action is less likely to promote AMR. In the present study, we tested two AMPPs (lysozyme and nisin; 50 and 500 µg/mL) as possible substitutes of gentamicin for boar semen preservation up to 48 h of storage. RESULTS: We found that both AMPPs improved sperm plasma membrane and acrosome integrity during semen storage. The highest concentration tested for lysozyme also kept the remaining sperm parameters unaltered, at 48 h of semen storage, and reduced the bacterial load at comparable levels of the samples supplemented with gentamicin (p > 0.05). On the other hand, while nisin (500 µg/mL) reduced the total Enterobacteriaceae counts, it also decreased the rapid and progressive sperm population and the seminal oxidation-reduction potential (p < 0.05). CONCLUSIONS: The protective effect of lysozyme on sperm function together with its antimicrobial activity and inborn presence in body fluids, including semen and cervical mucus, makes this enzyme a promising antimicrobial agent for boar semen preservation.
Keywords: Animals; gentamiciny; Gentamicin; Antimicrobial Peptides; spermie; Semen; Spermatozoa; nisin; Semen Preservation; Antimicrobial resistance; Anti-Bacterial Agents; prasata; antimikrobiální peptidy; Muramidase; Acrosome; sperma; Gentamicins; Lysozyme; Boar semen; Sperm function; Male; Swine; muramidasa; akrozom; mužské pohlaví; zvířata; antibakteriální látky; buněčná membrána; Nisin; uchování spermatu; Cell Membrane